Application of black cumin (Nigella sativa L.) seeds for the removal of metal ions and methylene blue from aqueous solutions. Issue 1 (31st December 2022) - Thabede, Patience Mapule; Shooto, Ntaote David
Abstract: This paper reviews the use of black cumin seeds (BCS), also known as Nigella sativa L., as an adsorbent for the sorption of harmful pollutants and methylene blue (MB) dye in aqueous solutions. Information for the adsorption of cobalt-Co(II), nickel-Ni(II), copper-Cu(II), chromium-Cr(VI), lead-Pb(II), cadmium-Cd(II) and methylene blue (MB) from aqueous solutions using black cumin seeds are discussed. The Brunauer–Emmett–Teller (BET) surface area of pristine seeds of 2.7 m 2 /g increased to 10.1, and 9.3 m 2 /g for KMnO4 and H3 PO4 treated seeds, respectively. Activation of the BCS with 10% and 20% H2 SO4 increased the surface area to 20.14 and 21.54 m 2 /g, respectively. Seeds activated with 20% H2 SO4 showed larger pore width of 7.13 nm compared to 6.81 nm for 10% H2 SO4 . Seeds treated with HCl and NaOH for quaternary adsorption studies showed that the maximum capacity for base treated-BCS was 190.7 mg/g whilst acid treated-BCS showed capacities of 180.1. Pristine seeds, H3 PO4 and KMnO4 treated seeds showed that the trend for the removal of Cr(VI) ions was KMnO4 > H3 PO4 > pristine with capacities of 16.12, 15.98 and 10.15 mg/g, respectively. Magnetite-sucrose functionalized seeds and pristine seeds had adsorption capacities for Cr(VI) were 15.6 and 13.0 mg/g, respectively. The same adsorbents had maximum sorption capacities of 39.7 and 37.9 mg/g for Pb(II) ions, respectively. The effectiveness of the defatted BCS using acetone and N, N dimethylformamide (DMF) showed that the acetone treated BCS had higher sorption capacities of 99.82 mg/g for MB, 96.89 m/g for Cd(II), and 87.44 mg/g for Cr(VI) compared to DMF treated seeds.